The Integration of Public Information Systems (PIS) in Fraud Prevention within Government Agencies - Aisyah, Amanda Putri; Prihandiki, Alfan; Zahira, Zaskia; Irawan (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
The integration of Public Information Systems (PIS) plays a key role in enhancing transparency and preventing fraud within government agencies. This study analyzes the effect of PIS integration on fraud prevention by incorporating information quality and government accountability as mediating variables. The research employs a quantitative approach using PLS-SEM (SmartPLS). Data were collected from government employees who utilize PIS in administrative and financial management processes. The results indicate that PIS integration has a significant effect on information quality and government accountability. Both information quality and accountability are also shown to have a positive influence on fraud prevention. Meanwhile, the direct effect of PIS integration on fraud prevention is relatively moderate but becomes stronger through the mediating roles of these two variables. These findings emphasize that the effectiveness of PIS in preventing fraud is highly dependent on the accuracy of information and the accountability mechanisms generated by the system. This study implies that government agencies need to strengthen system integration, enhance interoperability, and ensure information reliability to sustainably reinforce fraud prevention efforts.